1997
DOI: 10.1021/ma970555n
|View full text |Cite
|
Sign up to set email alerts
|

Determining Microscopic Viscoelasticity in Flexible and Semiflexible Polymer Networks from Thermal Fluctuations

Abstract: We have developed a new technique to measure viscoelasticity in soft materials such as polymer solutions, by monitoring thermal fluctuations of embedded probe particles using laser interferometry in a microscope. Interferometry allows us to obtain power spectra of fluctuating beads from 0.1 Hz to 20 kHz, and with subnanometer spatial resolution. Using linear response theory, we determined the frequency-dependent loss and storage shear moduli up to frequencies on the order of a kHz. Our technique measures local… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
400
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(428 citation statements)
references
References 49 publications
(94 reference statements)
25
400
2
1
Order By: Relevance
“…Qr, 82.70.ÿy, 83.60.Bc, 83.85.Ei Significant progress has been made over the past decade in developing optical microrheology as a noninvasive means to study the rheological properties of soft complex fluids. Following the seminal Letter of Mason and Weitz in 1995 [1], several hundred studies have reported on the application of optical microrheology to such diverse systems as polymers, emulsions, gels, biomaterials, hydrogel scaffolds, stomach mucus, magnetic fluids, ceramics, slurries, and many more [1][2][3][4][5]. The underlying idea is to study the response of small (colloidal) particles embedded in the system under study.…”
mentioning
confidence: 99%
“…Qr, 82.70.ÿy, 83.60.Bc, 83.85.Ei Significant progress has been made over the past decade in developing optical microrheology as a noninvasive means to study the rheological properties of soft complex fluids. Following the seminal Letter of Mason and Weitz in 1995 [1], several hundred studies have reported on the application of optical microrheology to such diverse systems as polymers, emulsions, gels, biomaterials, hydrogel scaffolds, stomach mucus, magnetic fluids, ceramics, slurries, and many more [1][2][3][4][5]. The underlying idea is to study the response of small (colloidal) particles embedded in the system under study.…”
mentioning
confidence: 99%
“…[29]. In the Newtonian limit for which (20) applies, one recovers from Eq. (21) the result given by Mazur and Bedeaux in Ref.…”
Section: Faxén's Theoremmentioning
confidence: 84%
“…In these experiments, the video tracking of the position of a diffusing Brownian particle is used in order to infer the viscoelastic properties of the media. Many new techniques have appeared for the study of such fluids involving embedded colloidal particles, such as one-particle [18][19][20][21], two-particle [22][23][24], and many-particle microrheology [25,26] as well as optical tweezers [27,28]. The extraction of the viscoelastic properties from the diffusion of the particles is done through a generalized Stokes-Einstein relation (GSER), which is a heuristic approximate expression relating the particle mean square displacement with the complex modulus of the suspending fluid.…”
Section: Introductionmentioning
confidence: 99%
“…For each set of data, PSD is calculated. 7,8 Figure 2 shows the PSD values of the trapped particles embedded in (a) Bacillus subtilis-active cells suspension and (b) Pseudomonas°uorescens-active cells suspension at di®erent cell counts. The data shown in this plot for both samples are a normalized average of 25 data sets collected at the same temperature and the same environment.…”
Section: Resultsmentioning
confidence: 99%